The Effect of Variation in Polyvinylpyrrolidone (PVP) Concentration as a Binder in The Formulation of Curcumin Isolate Lozenges - Yola Desnera Putri; Annisa Putri Dewantara; Yeyet Cahyati Sumirtapura; Adit Andriyannto (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: The pharmaceutical industry continues to develop user-friendly dosage forms to improve patient compliance, especially for individuals who have difficulty swallowing conventional tablets. Lozenges are an alternative oral dosage form that does not require water and allows drug absorption through the oral mucosa, making them more practical and convenient. In lozenge formulation, polyvinylpyrrolidone (PVP) as a binder plays an important role in determining physical characteristics such as hardness, friability, and disintegration time. Objective: This study aimed to evaluate the effect of varying PVP concentrations on the physical characteristics of curcumin isolate lozenges and to determine the optimal formulation. Methods: An experimental method using wet granulation was applied with PVP concentrations of 1%; 2%; 3%; 4% and 5%. Evaluations included granule properties (moisture content, flow rate, angle of repose, compressibility index) and tablet properties (organoleptic characteristics, weight and size uniformity, hardness, friability, and disintegration time). Results: Increasing PVP concentration influenced tablet characteristics, particularly hardness, friability, and disintegration time. All formulations met the physical quality requirements for lozenges. The formulation containing 3% PVP showed the most balanced characteristics compared to others. Conclusion: PVP concentration affects the physical properties of curcumin lozenges, with 3% identified as the optimal concentration, indicating its potential as a practical alternative oral dosage form.